Comparison of efficacy between robot-assisted laparoscopic and conventional laparoscopic radical prostatectomy and analysis on influencing factors - CHEN Qiming; CHEN Jian; LIU Qiuli (陆军军医大学学报)
Objective To compare the therapeutic efficacy of robot-assisted laparoscopic radical prostatectomy versus conventional laparoscopic radical prostatectomy, and analyze the factors influencing treatment outcomes. Methods A retrospective cohort study was conducted on 719 patients (total cohort) who underwent radical prostatectomy in our department from June 2002 to October 2023. According to different surgical methods, they were divided into robot-assisted laparoscopic radical prostatectomy group (robotic group, n=409) and conventional laparoscopic radical prostatectomy group (conventional group, n=310). Clinical characteristics, biochemical recurrence rates, and recovery of urinary continence at 1, 3, 6, and 12 months postoperatively, as well as sexual function recovery at 6 and 12 months after surgery, were compared between the 2 groups. Additionally, the factors influencing biochemical recurrence and urinary continence recovery were analyzed across the entire cohort. Results In the cohort, the robot group demonstrated significantly larger proportions of pathological high T stages (≥pT3, P < 0.01), increased positive lymph node rate (P < 0.01), and greater number of dissected lymph nodes (P < 0.01) than the conventional group. There were no statistical differences between the 2 groups in terms of Gleason score, biochemical recurrence rate, or incidence and type of complications. The robot group exhibited significantly higher rates of urinary continence recovery at 1 (P=0.004), 3 (P < 0.01), 6 (P=0.002) and 12 months (P=0.004) postoperatively. But no obvious difference was seen in the score of International Index of Erectile Function-5 (IIEF-5) between the 2 groups at 6 and 12 months. Across the entire cohort, pathological high T stage (≥pT3, P < 0.01), high Gleason score (>7, P=0.036), fewer lymph nodes dissected (≤10, P < 0.01), and positive lymph nodes (P=0.046) were independent risk factors for biochemical recurrence. Additionally, the surgical method, specifically robot-assisted laparoscopic radical prostatectomy, was identified as a significant factor influencing urinary continence recovery at 12 months postoperatively (P=0.005). Conclusion Compared to conventional laparoscopic radical prostatectomy, robot-assisted laparoscopic radical prostatectomy shows certain effect on reducing biochemical recurrence rate and enhancing recovery of urinary continence in prostate cancer patients at 1, 3, 6 and 12 months postoperatively.